Analisis Kemampuan Pemahaman Konsep Siswa Kelas IV SD UPT SDN 185 Gresik pada Materi Perkalian ditinjau dari Gaya Belajar dan Jenis Kelamin - Klasih Anur Pangayoman; Arissona Dia Indah Sari; Ismail Marzuki (Lembaga Pengembangan Kinerja Dosen, 2026)
Understanding mathematical concepts is a fundamental ability that elementary school students must possess, particularly in multiplication, which serves as a foundation for learning more advanced mathematical topics. Based on the conditions observed in the fourth-grade class at UPT SDN 185 Gresik, there are still students who do not fully understand the concept of multiplication, as the learning process tends to emphasize memorization rather than conceptual understanding. In addition, differences in learning styles and gender are suspected to influence students’ conceptual understanding abilities. Therefore, this study aims to describe the conceptual understanding of fourth-grade students in multiplication, viewed from their learning styles and gender.This study employs a descriptive qualitative research method, with six fourth-grade students of UPT SDN 185 Gresik as the research subjects. Data were collected through learning style questionnaires, concept understanding tests and questionnaires, and interviews. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, based on indicators of conceptual understanding. Data validity was ensured using triangulation of techniques, sources, and time. The results of the study indicate that auditory learners tend to have better conceptual understanding compared to visual and kinesthetic learners, and female students outperform male students. Based on these findings, teachers need to implement differentiated instruction tailored to students’ learning styles: using diagrams, images, and colored multiplication tables for visual learners; applying discussions, question-and-answer sessions, and repeated verbal explanations for auditory learners; and utilizing concrete teaching aids along with hands-on activities for kinesthetic learners to optimize conceptual understanding.